2017
DOI: 10.1017/wsc.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

Isoxadifen-Ethyl Derivatives Protect Rice from Fenoxaprop-P-Ethyl–associated Injury during the Control of Weedy Rice

Abstract: Fenoxaprop-P-ethyl, a phenoxy herbicide of the aryloxy–phenoxy–propionic acid group, had a strong control effect when applied POST to weedy rice in this study, with the effective concentrations of 294 μM and 218 μM of herbicide causing 50% inhibition (IC50) in plant height and fresh weight values, respectively. However, fenoxaprop-P-ethyl caused phytotoxicity in cultivated rice. Isoxadifen-ethyl, a widely used herbicide safener in rice, can decrease the phytotoxicity caused by fenoxaprop-P-ethyl. Owing to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…It is a highly selective stem and leaf treatment agent. , However, due to the long-term and widespread use of FE, crops suffer varying degrees of phytotoxicity. The application of FE results in crop yellowing, crop growth inhibition, and even crop death in serious cases. To reduce damage to crops, many methods have been reported that incorporate the scientific management of crop rotation and cultivation and the research and development of new herbicides. , In addition, the use of herbicide safeners is also considered to be an efficient solution. …”
Section: Introductionmentioning
confidence: 99%
“…It is a highly selective stem and leaf treatment agent. , However, due to the long-term and widespread use of FE, crops suffer varying degrees of phytotoxicity. The application of FE results in crop yellowing, crop growth inhibition, and even crop death in serious cases. To reduce damage to crops, many methods have been reported that incorporate the scientific management of crop rotation and cultivation and the research and development of new herbicides. , In addition, the use of herbicide safeners is also considered to be an efficient solution. …”
Section: Introductionmentioning
confidence: 99%
“…22,[42][43][44] The safener isoxadifen-ethyl allows the selective use of fenoxaprop-p-ethyl in rice. 15,45 The effect of this safener occurs for multiple crops for multiple herbicide modes of action, such as rice to fenoxapropp-ethyl, 45 corn to foramsulfuron 46 and tembotrione. 47 Another safener, fenclorim, can protect rice from injury when sprayed with the herbicide pretilachlor, but it does not protect E. crus-galli.…”
Section: Discussionmentioning
confidence: 99%
“…Safener pathways of induction are not well understood, but studies suggest that they are related to cytP450, GST, glycosyl‐transferase (GT) and ABC transporter enzymes 22,42–44 . The safener isoxadifen‐ethyl allows the selective use of fenoxaprop‐ p ‐ethyl in rice 15,45 . The effect of this safener occurs for multiple crops for multiple herbicide modes of action, such as rice to fenoxaprop‐ p ‐ethyl, 45 corn to foramsulfuron 46 and tembotrione 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Each experiment was repeated in triplicate and a completely randomized design was used. The injury recovery rate (IRR) was calculated as follows 39 Injury Recovery Rate0.5em()%=Treated with safener and herbicideTreated with herbicide0.25em0.25emContrastTreated with herbicide×100% …”
Section: Methodsmentioning
confidence: 99%